The relationship between quality of life, sleep quality, mental health, and physical activity in an international sample of college students: a structural equation modeling approach - Moussa-Chamari, Imen; Farooq, Abdulaziz; Romdhani, Mohamed; Washif, Jad Adrian; Bakare, Ummukulthoum; Helmy, Mai; Al-Horani, Ramzi A.; Salamh, Paul; Robin, Nicolas; Hue, Olivier (Frontiers in Public Health, 2024)
Objective: We assessed the direct and indirect relationships between sleep quality, mental health, and physical activity with quality of life (QOL) in college and university students. Methods: In a cross-sectional design, 3380 college students (60% females; age= 22.7±5.4) from four continents (Africa: 32%; America: 5%; Asia: 46%; and Europe: 15%; others: 2%) completed the Pittsburgh Sleep Quality Index (PSQI); Insomnia Severity Index (ISI); Epworth Sleepiness Scale (ESS); the Depression, Anxiety, and Stress Scale 21 (DASS); the International Physical Activity Questionnaire short-form (IPAQ); and the World Health Organization Quality Of Life-BREF (WHOQOL-Brief). Results: We showed that sleep quality, insomnia, and depression had direct negative effects on the physical domain of QOL (β= -0.22, -0.19, -0.31, respectively, p < 0.001). There was a strong negative direct association between depression and the psychological domain of QOL (β=-0.60, z = -22.21, p < 0.001). Both stress and PSQI had direct effects on social relationships QOL (β = 0.11; z = 4.09; and β = -0.13; z = -7.40, respectively, p < 0.001). However, depression had the strongest direct impact on social relationships QOL (β = -0.41, z = -15.79, p < 0.001). Conclusion: The overall QOL of university students is associated with their sleep quality, mental health, and physical activity warranting further interventional studies aiming at improving students’ quality of life.